2019
DOI: 10.1038/s41467-019-09218-6
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-strong long-chain polyamide elastomers with programmable supramolecular interactions and oriented crystalline microstructures

Abstract: Polyamides are one of the most important polymers. Long-chain aliphatic polyamides could bridge the gap between traditional polyamides and polyethylenes. Here we report an approach to preparing sustainable ultra-strong elastomers from biomass-derived long-chain polyamides by thiol-ene addition copolymerization with diamide diene monomers. The pendant polar hydroxyl and non-polar butyrate groups between amides allow controlled programming of supramolecular hydrogen bonding and facile tuning of crystallization o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
99
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 155 publications
(104 citation statements)
references
References 57 publications
(39 reference statements)
2
99
0
Order By: Relevance
“…The latter two features indicated the formation of hydrogen bonds between polymer chains. [ 57 ] The peaks at 1685 cm −1 of PPS1 and PPS2 increased in intensity compared with those of PU , and the peak intensities at 1715 and 1660 cm −1 decreased. These changes indicated that the large PS groups disrupted the PU chain regularity and weakened the hydrogen bonds.…”
Section: Figurementioning
confidence: 99%
“…The latter two features indicated the formation of hydrogen bonds between polymer chains. [ 57 ] The peaks at 1685 cm −1 of PPS1 and PPS2 increased in intensity compared with those of PU , and the peak intensities at 1715 and 1660 cm −1 decreased. These changes indicated that the large PS groups disrupted the PU chain regularity and weakened the hydrogen bonds.…”
Section: Figurementioning
confidence: 99%
“…Thermoplastic polymers exhibiting a combination of high mechanical strength, good recyclability, processability, and thermal/mechanical durability have received much attention in scientific research and industrial applications. [1][2][3][4][5][6][7][8][9][10] Although strategies such as alignment of polymer chains, crystallization, controlled phase separation, interpenetrating, and dual polymer networks could significantly enhance the mechanical strength of thermoplastic polymers, 4,7,[11][12][13] it is hard for their tensile strength to reach or exceed one hundred megapascals (MPa). 4,7,10,[11][12][13] Meanwhile, superstrong thermoplastic polymers are usually difficult to dissolve in proper solvents and to process.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10] Although strategies such as alignment of polymer chains, crystallization, controlled phase separation, interpenetrating, and dual polymer networks could significantly enhance the mechanical strength of thermoplastic polymers, 4,7,[11][12][13] it is hard for their tensile strength to reach or exceed one hundred megapascals (MPa). 4,7,10,[11][12][13] Meanwhile, superstrong thermoplastic polymers are usually difficult to dissolve in proper solvents and to process. 3,5,14,15 A conventional and widely employed strategy for reinforcement of thermoplastic polymers is homogeneously dispersing stiff nanofillers, such as silica, 9,16 clays, 10,17,18 carbon nanotubes, [19][20][21] graphene oxides, 20,[22][23][24] cellulose nanocrystals, 25,26 metal nanoparticles, 27,28 and other nanofillers 3,[29][30][31] within them.…”
Section: Introductionmentioning
confidence: 99%
“…[17] Preparation of sustainable ultra-strong elastomers from biomass-derived long-chain polyamides by thiolene addition copolymerization with diamide diene monomers was recently discussed as well. [18] More recently, poly(amide thioether)s with crystallinity more than 95 % were prepared by addition of ethanedithiol to diallylamides. [19] These approaches became possible due to available monomeric base from natural products.…”
Section: Introductionmentioning
confidence: 99%
“…Degradable polymers were synthesized with thiol‐(meth)acrylate or acrylamide by one‐pot polyaddition and based on cysteamine with 10‐undecenoate, methyl oleate . Preparation of sustainable ultra‐strong elastomers from biomass‐derived long‐chain polyamides by thiol‐ene addition copolymerization with diamide diene monomers was recently discussed as well . More recently, poly(amide thioether)s with crystallinity more than 95 % were prepared by addition of ethanedithiol to diallylamides .…”
Section: Introductionmentioning
confidence: 99%